Determination of the weld metal corrosion rate using electrochemical techniques - Bore Jegdić; Nikola Bajić (Zaštita Materijala)
To determine corrosion rate of the base metal and weld metal were applied electrochemical techniques: linear polarization resistance, linear sweep voltammetry and electrochemical impedance spectroscopy. The samples were obtained by arc welding steel boiler plate using coated basic electrode. Factory electrode and electrodes, which are produced in the laboratory thinly and thick coated basic electrodes, were used for welding. It was found that the corrosion rate of the weld metal was greater than the corrosion rate of the base metal. The corrosion rate of weld metal obtained by thinly coated electrodes is less than the corrosion rate of weld metal obtained by thick coated basic and factory-coated electrodes. The corrosion rates, determined by different electrochemical techniques are in agreement.